A Stable Crystalline N‐Heterocyclic Carbene with a 1, 1'‐Ferrocenylene Backbone and Benzylic N‐Substituents. Issue 4 (16th December 2022) - Zinke, Julian; Bruhn, Clemens; Siemeling, Ulrich
Abstract: Two ferrocene‐based NHCs of the type fc[(NR)2 C:] (1 R ; fc=1, 1'‐ferrocenylene) containing benzylic N ‐substituents were synthesised from the corresponding formamidinium compounds 1 R H[BF4 ] by reaction with LiN(SiMe3 )2 . In the case of R=CH2 Ph (Bn), the carbene was characterised through trapping reactions with sulfur and selenium, which afforded fc[(NBn)2 CS] (1 Bn S) and fc[(NBn)2 CSe] (1 Bn Se), respectively. A thermally stable carbene was obtained with R=CH2 Mes (Bn*). Its reaction with sulfur and selenium afforded fc[(NBn*)2 CS] (1 Bn* S) and fc[(NBn*)2 CSe] (1 Bn* Se), respectively. Its reaction with [Rh(μ‐Cl)(COD)]2 (COD=cycloocta‐1, 5‐diene), followed by substitution of the COD ligand by CO, furnished cis ‐[RhCl(CO)2 (1 Bn* )]. In combination with IR data of cis ‐[RhCl(CO)2 (1 Bn* )], NMR data of 1 Bn* H[BF4 ], 1 Bn* and 1 Bn* Se indicate that 1 Bn* is substantially more nucleophilic and more electrophilic than conventional Arduengo carbenes, exhibiting an ambiphilicity similar to that of CAACs. The crystal structures of the formamidinium salts 1 R HX (X=[BF4 ], R=Bn, Bn*; X=Cl, R=Bn*), of the carbene 1 Bn* and its Au I complex [AuCl(1 Bn* )] as well as of the sulfur and selenium derivatives 1 R E (E=S, Se; R=Bn, Bn*), the Rh I complexes cis ‐[RhCl(CO)2 (1 R )] (R=Bn, Bn*) and the Cu I complex [CuBr(1 Bn )] were determined by single‐crystal X‐ray diffraction (XRD). In addition, the crystals structures of the diimine fc(N=CHMes)2 and the diamine fc(NHBn*)2 were also determined by XRD. Abstract :